Understanding Olympic speedskating: effects of ice, skates, gender differences, percent improvements - Stefani, R. (Calinornia State University, 2018)
Olympic speed skating champions at the 2018 Winter Olympics finally produced times as good as at Salt Lake in 2002, when ice conditions were exceptional. The causes of improvement in speed skating will be deduced and evaluated. Olympic speed skating began for men in 1924 and for women in 1960. An athlete produces power due to lean body mass and training. The efficiency of applying that power depends on coaching, technique and equipment (including the aerodynamics of the suit, skates and ice conditions). Technicians created outstanding ice conditions at Cortina in 1956, at Lake Placid in 1980 and at Salt Lake in 2002. Competition moved indoors at Calgary in 1988 where ice was not subject to the whims of weather, back outdoors in 1992 and back indoors (with better ice) for good in 1994. The clap skate was introduced in 1998. That skate allowed powerful extensor muscles to be used for the first time, as the skate remained in contact with the ice for a greater fraction of the power stroke. A linear regression analysis of Olympic winning times showed that the percent improvement per Olympiad (%I/O) was 0.8% due to general improvements in training and efficiency. An additional 3.3% was added for each of the five Games when ice improved, 4.2% was lost when competition moved back outdoors and an additional 2.1% was gained when the clap skate was introduced. A plot of the velocity ratio of the female/male Olympic champions shows an exponential increase from 87.5% in 1960, flattening out at 92% in 1980, as training and efficiency for women improved relative to men. The average %I/O has remained at 92% since 1980. Assuming equal training and efficiency, the 92% female/male velocity ratio should equal the female/male relative lean-to-weight ratio of elite speed skaters, which it does.